High-Molecular-Weight Fractions of Spruce and Eucalyptus Lignin as a Perspective Nanoparticle-Based Platform for a Therapy Delivery in Liver Cancer - Pylypchuk, Ievgen V.; Suo, Huizhen; Chucheepchuenkamol, Chanakarn; Jedicke, Nils; Lindén, Pär A.; Lindström, Mikael E.; Manns, Michael P.; Sevastyanova, Olena; Yevsa, Tetyana (Frontiers in Bioengineering and Biotechnology, 2022)
The natural polymer, lignin, possesses unique biodegradable and biocompatible properties making it highly attractive for the generation of nanoparticles for targeted cancer therapy. In this study, we investigated spruce and eucalyptus lignin nanoparticles (designated as S- and E-LNPs, respectively). Both LNP types were generated from high-molecular-weight (Mw) kraft lignin obtained as insoluble residues after a five-step solvent fractionation approach, which included ethyl acetate, ethanol, methanol and acetone. The resulting S-and E-LNPs ranged in size from 16 to 60 nm with uniform spherical shape regardless of the type of lignin. The preparation of LNPs from an acetone-insoluble lignin fraction is attractive because of the use high-Mw lignin that is otherwise not suitable for most polymeric applications, its potential scalability, and due to the consistent size of the LNPs, which was independent of increased lignin concentrations. Due to the potential of LNPs to serve as delivery platforms in liver cancer treatment, we tested, for the first time, the efficacy of newly generated E-LNPs and S-LNPs in two types of primary liver cancer, hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA) in vitro. Both S-LNPs and E-LNPs inhibited the proliferation of HCC cells in a dose-dependent manner and did not affect CCA cell line growth. The inhibitory effect towards HCC was more pronounced in the E-LNPs-treated group and was comparable to the standard therapy, sorafenib. Also, E-LNPs induced late apoptosis and necroptosis while inhibiting the HCC cell line. This study demonstrated that an elevated number of carbohydrates on the surface of the LNPs, as shown by NMR, seems to play an important role in mediating the interaction between LNPs and eukaryotic cells. The latter effect was most pronounced in E-LNPs. The novel S- and E-LNPs generated in this work are promising materials for biomedicine with advantageous properties such as small particles size, and tailored surface functionality, making them an attractive and potentially biodegradable delivery tool for combination therapy in liver cancer, that still has to be verified in vivo using HCC and CCA models.